PENINGKATAN KUALITAS PELAYANAN PADA KANTOR KELURAHAN MANGGALA MELALUI PENYUSUNAN STANDAR OPERASIONAL PROSEDUR - Dalaiya, Andi; Musdalifah, Musdalifah (Politeknik STIA LAN Makassar, 2023)
Public service is a form of service in the form of public goods and public services that are the responsibility and are carried out by the government in order to fulfill the needs of the community and in the context of implementing the provisions of laws and regulations. If the public services provided to the community are effective and efficient, the community feels the good quality of service from the public servant organizers, so the need for Standard Operating Procedures (SOP) as a guideline that can facilitate service providers in providing services, especially government organizations, with Standard Operating Procedures, government administration can run with certainty. The purpose of this research is the preparation of Standard Operating Procedures for services at the Manggala Village Office in improving the quality of services provided. The preparation of Standard Operating Procedures has been prepared using the methods of observation, interview and document review. This research produces the final work in the form of Standard Operating Procedures, there are five procedures that will be made SOPs including, death information, temporary domicile information, information on incapacity, marriage introduction and business information. There are several stages carried out in the preparation of the SOP, namely conducting a needs assessment by determining the service procedures to be made, then the stages of making the SOP by collecting related information and then making it in accordance with the guidelines, finally reviewing and socializing with the executor of the servant related to the SOP that has been made.